2000
DOI: 10.2337/diabetes.49.7.1258
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating nitric oxide in young patients with type 1 diabetes and persistent microalbuminuria: relation to glomerular hyperfiltration.

Abstract: Hyperglycemia has been causally linked to vascular and glomerular dysfunction by a variety of biochemical mechanisms, including a glucose-dependent abnormality in nitric oxide (NO) production and action. NO is a candidate for mediating hyperfiltration and the increased vascular permeability induced by diabetes. Serum nitrite and nitrate (NO 2 -+ NO 3 -) concentrations were assessed as an index of NO production in 30 adolescents and young adults with type 1 diabetes, 15 with and 15 without microalbuminuria (alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 38 publications
9
79
2
Order By: Relevance
“…Experimental data from the single nephron model has demonstrated that NO contributes to efferent arteriolar tone (23). Our conclusion of a decreased efferent NO bioavailability in diabetic subjects that is potentially ameliorated by rosiglitazone appears to be in conflict with studies suggesting a contribution of increased NO to the glomerular hyperfiltration in the early diabetic state (24,25). These studies, however, did not test bioavailable NO (e.g., by assessment of renal hemodynamics).…”
Section: Discussioncontrasting
confidence: 52%
“…Experimental data from the single nephron model has demonstrated that NO contributes to efferent arteriolar tone (23). Our conclusion of a decreased efferent NO bioavailability in diabetic subjects that is potentially ameliorated by rosiglitazone appears to be in conflict with studies suggesting a contribution of increased NO to the glomerular hyperfiltration in the early diabetic state (24,25). These studies, however, did not test bioavailable NO (e.g., by assessment of renal hemodynamics).…”
Section: Discussioncontrasting
confidence: 52%
“…The haemodynamic hypothesis of diabetic microangiopathy emphasises the importance of increases in capillary pressure and flow as key factors for the development of complications [30]. Enhanced endothelial nitric oxide synthase (eNOS) activity has been suggested to mediate renal hyperfiltration [31]. Indeed, chronic NOS inhibition abolishes glomerular hyperfiltration [32], and the afferent arterioles of streptozotocin diabetic rats show high levels of eNOS expression [33].…”
Section: Discussionmentioning
confidence: 99%
“…A lterations in renal hemodynamic function are prevalent in diabetes (1,2) and include increased intraglomerular capillary pressure and hyperfiltration (3)(4)(5). Because blockade of the renin angiotensin system (RAS) does not completely normalize hyperfiltration (6), it is clear that other factors are operative in the renal microcirculation in diabetes.…”
mentioning
confidence: 99%